Pengaruh Self Atribution Bias, Mental Accounting, Familiarity Bias, Terhadap Pengambilan Keputusan Investasi (Studi kasus, Mahasiswa FEB UDINUS SEMARANG): Pengaruh Self Atribution Bias, Mental Accounting, Familiarity Bias, Terhadap Pengambilan Keputusan Investasi (Studi kasus, Mahasiswa FEB UDINUS SEMARANG) - vioneta cattravelly Pandji; Entot Suhartono; Nila Tristiarini; Melati Oktafiyani (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
Abstract. This study aims to examine the influence of Influence, Mental Accounting, Familiarity Bias, Self Attribution Bias on Investment Decision Making by providing evidence of an increasing number of investors in the capital market, especially among students. This research was conducted by Udinus Semarang using a questionnaire instrument that was processed using Regression Analysis, to Hypothesis Test. The results showed the influence of Mental Accounting, Familiarity Bias, Self Attribution Bias on Investment Decision Making shown by the increase or increase in the number of investors in Indonesia, especially in the young investor or student category Keywords: Mental Accounting, Familiarity Bias, Self Attribution Bias, and Investment Decision Making